Triassic-Jurassic weathering and clay mineral dispersal in basement areas and sedimentary basins of southern Sweden - Ahlberg, Anders; Olsson, Ingela; Simkevicius, Petras (Sedimentary Geology, 2003)
The basement rocks of southern Sweden were deeply weathered in Late Triassic through Cretaceous times, and possibly even earlier. Sub-Mesozoic saprolites formed, presumably due to long-term warmth and humidity, in conjunction with decomposition of abundant organic matter and subsequent infiltration of acidic water. The upper parts of the weathering profiles were subjected to intense leaching and kaolinitisation whereas the less evolved deep weathering front is enriched in smectite. Thus. any erosion prior to full regolith development, or extraordinary deep erosion, released less developed, smectite-rich weathering material to the Late Triassic-Jurassic receiving basins. Mesozoic sedimentary successions in Southern Sweden show high detrital smectite and/or kaolinite contents, moderate illite contents and low chlorite contents, compatible with expected mid-latitude warm equable greenhouse conditions. Norian and older Triassic haematite-cemented continental arkoses and smectite-dominated clays (smectitemuch greater thankaolinite) were clearly formed in and settings. Front the Rhaetian and throughout the Jurassic, humid onshore conditions sustained abundant plant and peat accumulation, early diagenetic meteoric flushing, and intense chemical weathering. Kaolinite is therefore a dominating detrital clay mineral in these sedimentary successions (kaolinite = illitemuch greater thanchlorite and smectite (I/S)). Minor quantitative variations in clay mineralogy within the "humid climate" Rhaetian-Jurassic sedimentary successions are difficult to interpret. In deltaic coal-bearing successions, the detrital clay mineral composition is conspicuously constant (kaolinite = illite-chlorite), possibly due to post-depositional clay mineral transformation. Conversely, in shallow marine deposits, some quantitative variation is notable (kaolinite approximate to illite>variable smectitemuch greater thanchlorite). This may reflect that the original detrital composition was better preserved in shallow marine settings. Smectitic clay ...